Sistem Pendukung Keputusan Penilaian Kinerja Tenaga Honor Panitia Pengawas Menggunakan Kombinasi Logarithmic Least Squares Weighting dan MABAC - Mahendra, Ferdian Jerry; Setiawansyah, Setiawansyah (Journal of Computer System and Informatics (JoSYC), 2024)
The performance of the honor staff, supervisory committee, division, staff handling violations, dispute resolution is vital in ensuring effectiveness and fairness in handling violations and dispute resolution within the organization. The main problems in evaluating the performance of supervisory committee personnel include subjectivity in the assessment, and lack of transparency in the appraisal process. Subjectivity can arise due to different perceptions of the party making the assessment, which can lead to unfairness in performance evaluation. Non-transparency in the appraisal process can also raise doubts and distrust of the fairness of the performance appraisal process of supervisory staff. DSS performance appraisal of honorary personnel of the supervisory committee using a combination of LLSW and MABAC is to develop a holistic and effective approach in evaluating the performance of honorary personnel in the supervisory committee. This research is to improve objectivity and fairness in performance appraisal, as well as enable decision makers to make more informed and informed decisions in honorary personnel management in the supervisory committee. The combination of LLSW (Logarithmic Least Squares Weighting) and MABAC (Multi-Attributive Border Approximation Area Comparison) can obtain more detailed and objective recommendations in the performance assessment of honor personnel. This process combines a statistical approach (LLSW) to determine attribute weights and a multi-attribute comparative analysis (MABAC) to obtain a final alternative ranking. The results of ranking 3 alternatives using a combination of LLSW and MABAC methods in assessing the performance of honor workers showed that the results for rank 1 were obtained by Yustina with a final function value of 0.152406, rank 2 was obtained by Andri with a final function value of 0.118662, and rank 3 was obtained by Sudrajat with a final function value of 0.094245.